Genus Enterolobium : traditional uses, chemistry and biological activities - Mariam I. Gamal El-Din; Omayma A. Eldahshan; Abdel-Nasser B. Singab; Nahla A. A. Ayoub (Ain Shams University, 2017)
The chemical composition, pharmacological activity and traditional uses of 20 species attributed to the genus Enterolobium (Fabaceae) as used in the South and Central America, and Tropical Africa, were revised and compared. A survey of the available literature shows that these species are used mostly for their anti-inflammatory and cytotoxic activities. Additionally, some of these Enterolobium species showed antibacterial, antifungal, insecticidal, molluscicidal and larvicidal activities. Generally, the triterpenes or the phenolic compounds isolated from these plant extracts are assumed to be the bioactive principles.